Abnormal involuntary movement scale in tardive dyskinesia: Minimal clinically important difference. Issue 8 (24th June 2019) - Stacy, Mark; Sajatovic, Martha; Kane, John M.; Cutler, Andrew J.; Liang, Grace S.; O'Brien, Christopher F.; Correll, Christoph U.
Abstract: Background: A minimal clinically important difference has not been established for the Abnormal Involuntary Movement Scale in patients with tardive dyskinesia. Valbenazine is a vesicular monoamine transporter 2 inhibitor approved for the treatment of tardive dyskinesia in adults. Efficacy in randomized, double‐blind, placebo‐controlled trials was defined as the change from baseline in Abnormal Involuntary Movement Scale total score (sum of items 1‐7). Objectives: To estimate an minimal clinically important difference for the Abnormal Involuntary Movement Scale using valbenazine trial data and an anchor‐based method. Methods: Data were pooled from three 6‐week double‐blind, placebo‐controlled trials: KINECT (NCT01688037), KINECT 2 (NCT01733121), and KINECT 3 (NCT02274558). Valbenazine doses were pooled for analyses as follows: "low dose, " which includes 40 or 50 mg/day; and "high dose, " which includes 75 or 80 mg/day. Mean changes from baseline in Abnormal Involuntary Movement Scale total score were analyzed in all participants (valbenazine‐ and placebo‐treated) with a Clinical Global Impression of Change‐Tardive Dyskinesia or Patient Global Impression of Change score of 1 (very much improved) to 3 (minimally improved). Results: The least squares mean improvement from baseline to week 6 in Abnormal Involuntary Movement Scale total score was significantly greater with valbenazine (low dose: –2.4; high dose: –3.2; both, P  < 0.001) versus placebo (–0.7). An minimal clinically important difference of 2 points was estimated based on least squares mean changes in Abnormal Involuntary Movement Scale total score in participants with a Clinical Global Impression of Change‐Tardive Dyskinesia score ≤3 at week 6 (mean change: –2.2; median change: –2) or Patient Global Impression of Change score ≤3 at week 6 (mean change: –2.0; median change: –2). Conclusions: Results from an anchor‐based method indicate that a 2‐point decrease in Abnormal Involuntary Movement Scale total score may be considered clinically important. © 2019 The Authors. Movement Disorders published by Wiley Periodicals, Inc. on behalf of International Parkinson and Movement Disorder Society.